Peran Media Sosial Sebagai Sarana Komunikasi Pendidikan Bagi Mahasiswa Di Era Digital - Ere Mardella Arbiani; Abel Juraidah; Almaidah (Al-Qolamuna: Journal Komunikasi dan Penyiaran Islam, 2025)
This paper discusses the role of social media as a means of educational communication for students, particularly in relation to its impact on academic achievement. In the digital era, social media not only serves as a space for personal interaction but also has the potential to support academic activities through the dissemination of information, online discussions, and collaboration between students. However, the use of social media does not always have a positive impact. Based on the author's opinion, a real contribution to improving academic achievement only occurs when students consciously use social media for educational purposes, for example, by sharing course materials, discussing assignments, forming virtual study groups, or providing feedback among themselves. Conversely, non-academic communication activities, such as casual conversations or personal posts, do not significantly impact academic performance. This confirms that learning success is not determined by the intensity of social media use, but rather by the orientation, strategy, and quality of its use. Thus, social media has great potential as a means of educational communication, but its effectiveness depends on students' ability to direct its use toward activities that support the learning process. This conceptual thinking is expected to form the basis for further empirical research and serve as a reference for educational institutions in designing strategies to optimize social media as a support for student learning. Abstrak Tulisan ini membahas peran media sosial sebagai sarana komunikasi pendidikan bagi mahasiswa, khususnya dalam kaitannya dengan pengaruh terhadap prestasi akademik. Di era digital, media sosial tidak hanya berfungsi sebagai ruang interaksi personal, tetapi juga memiliki potensi mendukung kegiatan akademik melalui penyebaran informasi, diskusi daring, serta kolaborasi antar mahasiswa. Meski demikian, pemanfaatan media sosial tidak selalu memberikan dampak positif. Berdasarkan pemikiran penulis, kontribusi nyata terhadap peningkatan prestasi akademik hanya muncul ketika mahasiswa menggunakan media sosial secara sadar untuk tujuan pendidikan, misalnya berbagi materi kuliah, berdiskusi mengenai tugas, membentuk kelompok belajar virtual, atau memberikan umpan balik antar sesama. Sebaliknya, aktivitas komunikasi yang bersifat non-akademik, seperti percakapan ringan atau unggahan pribadi, tidak berpengaruh signifikan terhadap kinerja akademik. Hal ini menegaskan bahwa keberhasilan belajar tidak ditentukan oleh intensitas penggunaan media sosial, melainkan oleh orientasi, strategi, dan kualitas pemanfaatannya. Dengan demikian, media sosial memiliki potensi besar sebagai sarana komunikasi pendidikan, namun efektivitasnya bergantung pada kemampuan mahasiswa mengarahkan penggunaannya ke aktivitas yang mendukung proses belajar. Pemikiran konseptual ini diharapkan dapat menjadi landasan bagi penelitian empiris selanjutnya serta menjadi rujukan bagi lembaga pendidikan dalam merancang strategi optimalisasi media sosial sebagai pendukung pembelajaran mahasiswa.